Is there an association between glenoid parameters and rotator cuff tears and the influence of gender: A retrospective study on a Middle Eastern population. (2020) - Maalouly, Joseph; Tawk, Antonios; Aouad, Dany; Nour, Hicham Abdel; Saidy, Elias; Abboud, Ghadi; El Rassi, Georges
Highlights: The radiographic measurements of the glenoid parameters may be helpful when the clinical diagnosis is difficult to attain. These measurements can help in planning the management of cuff tears, especially in cases in which tears are resistant to treatment. The importance of these findings is using an individualized approach in the management of the rotator cuff tears that can be based on gender, age, and the biomechanics of the patient. Abstract: Objective: This study aims to investigate the presence of any differences between the normal population and patients with rotator cuff tears in term of glenoid morphological parameters. Method: For the purpose of this study, 82 shoulder MRIs were evaluated. The individuals included in this study were divided into the patient group (cuff tear group, n = 41) and the control group (control group, n = 41) with respect to the inclusion and exclusion criteria. For the statistical analysis, SPSS software was used. Results: Statistically significant difference was found between the patient group and the control group in terms of Glenoid Version Angle (GVA), Glenoid Axial Width (GAW), Glenoid Axial Depth (GAD), Glenoid Coronal Depth (GCD), and the Glenoid Inclination Angle (GIA). Age was found to have a positive linear correlation with the glenoid coronal height. Moreover, statistically significant difference was found between the males and females, between males with cuff tears and control males, and females with cuff tears and control females in terms of glenoid parameters. When gender was a covariate, statistically significant differences in glenoid parameters was still present between cuff tears patients and individuals with control shoulders. Conclusion: The results attained in this study are suggest that the GVA, GAW, GAD, GCD, and GIA in rotator cuff tear patients are different than those found in control patients. These measurements may be helpful in reaching the diagnosis in cases where the clinical diagnosis is equivocal. Moreover, these measurements may be helpful in planning tears management. The influence of gender on glenoid parameters and subsequent impact on shoulder pathology may help to better understand the biomechanism of rotator cuff tears and reach an individualized management for better patient care.